1978
DOI: 10.1002/jpln.19781410506
|View full text |Cite
|
Sign up to set email alerts
|

Umsatz und Wirkung von Harnstoff‐Dicyandiamid‐ sowie Ammonsulfat‐Dicyandiamid‐Produkten zu Weidelgras und Reis

Abstract: In der vorliegenden

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In a pot trial to test combination compounds of uredDCD resp. ammonium sulfate/DCD, losses of N by denitrification were higher with longer preincubation periods, consequently resulting in lower nitrogen uptake by plants (Amberger and Gutser 1978). With DCD, the denitrification losses decreased considerably and N uptake increased (table 11).…”
Section: Seed Quantity: 205 Kglhamentioning
confidence: 99%
“…In a pot trial to test combination compounds of uredDCD resp. ammonium sulfate/DCD, losses of N by denitrification were higher with longer preincubation periods, consequently resulting in lower nitrogen uptake by plants (Amberger and Gutser 1978). With DCD, the denitrification losses decreased considerably and N uptake increased (table 11).…”
Section: Seed Quantity: 205 Kglhamentioning
confidence: 99%
“…In recent years, there has been considerable interest in DCD as a means of increasing the efficiency of nitrogen applied to different crops (Amberger & Gutser, 1978;Amberger, 1981;Rieder & Michaud, 1981). Rieder (1981) reported that in Italy application of DCD with urea 7-21 days before flooding rice fields considerably increased the yield of rice as compared with urea not treated with DCD.…”
Section: Introductionmentioning
confidence: 99%
“…Dicyandiamide (DCD) (obtained from SKW Trostberg, West Germany, as Didin®) is an organic N compound [H 2 NC(NH)NHCN] which inhibits the cytochrome oxidase involved in NHt oxidation by Nitrosomonas bacteria. Applications of 10 mg DCD kg-1 soil have been shown to inhibit nitrification up to 40 days at 20°C (Amberger and Vilsmeier, 1979). Amberger and Gutser ( 1979) reported inhibition of nitrification of urea and NHiS0 4 h for 10 weeks, with 20% ofthe N as DCD.…”
mentioning
confidence: 99%
“…Applications of 10 mg DCD kg-1 soil have been shown to inhibit nitrification up to 40 days at 20°C (Amberger and Vilsmeier, 1979). Amberger and Gutser ( 1979) reported inhibition of nitrification of urea and NHiS0 4 h for 10 weeks, with 20% ofthe N as DCD. At a DCD rate of2.5% of total fertilizer N, Jurkowska (1971) measured significant reductions in N03 concentration in spinach (Spinacia oleracea L.) leaves.…”
mentioning
confidence: 99%